2013
DOI: 10.1103/physrevb.87.060302
|View full text |Cite
|
Sign up to set email alerts
|

Magnetization precession induced by quasitransverse picosecond strain pulses in (311) ferromagnetic (Ga,Mn)As

Abstract: Quasi-longitudinal and quasi-transverse picosecond strain pulses injected into a ferromagnetic (311) (Ga,Mn)As film induce dynamical shear strain in the film, thereby modulating the magnetic anisotropy and inducing resonant precession of the magnetization at a frequency ~10 GHz. The modulation of the out-of-plane magnetization component by the quasitransverse strain reaches amplitudes as large as 10% of the equilibrium magnetization. Our theoretical analysis is in good agreement with the observed results, thus… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
30
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 24 publications
0
30
0
1
Order By: Relevance
“…[42] (see Fig.1 (a)). The strong demagnetization field Bd and in-plane direction of the external magnetic field B bring the equilibrium magnetization to the film plane.…”
Section: Appendix B Laser-pulse Induced Magnetization Precessionmentioning
confidence: 99%
“…[42] (see Fig.1 (a)). The strong demagnetization field Bd and in-plane direction of the external magnetic field B bring the equilibrium magnetization to the film plane.…”
Section: Appendix B Laser-pulse Induced Magnetization Precessionmentioning
confidence: 99%
“…4(c)] (M x → M x and M y → −M y , which is equivalent to φ → −φ), the direction of magnetization precession changes in accordance with the above equation. We note that the foregoing discussion on magnetoelasticity is related to a myriad of other ultrafast [17][18][19][20][21][22] work as well as its connection to quasistatic straintronics [23,24].…”
Section: Experimental Techniquementioning
confidence: 99%
“…Periodic arrays of non-magnetic materials, on the other hand, were shown to exhibit oscillations in their time-dependent reflectivity due to the generation of elastic waves in these phononic crystals [10,11]. Several groups have recently observed that acoustic waves can trigger magnetization precessions and even switching in continuous magnetic films via magneto-elastic coupling [12][13][14][15][16][17][18]. However, the interplay between phononic and magnetic modes generated in nanostructured array and its effect on the magnetization dynamics of a nanomagnet has not been investigated.…”
mentioning
confidence: 99%